2015
DOI: 10.1080/00224499.2014.980497
|View full text |Cite
|
Sign up to set email alerts
|

Harassment Due to Gender Nonconformity Mediates the Association Between Sexual Minority Identity and Depressive Symptoms

Abstract: The visibility of a stigmatized identity is central in determining how individuals experience that identity. Sexual minority status (e.g., identifying as gay, lesbian, or bisexual) has traditionally been identified as a concealable stigma, compared with race/ethnicity or physical disability status. This conceptualization fails to recognize, however, the strong link between sexual minority status and a visible stigma: gender nonconformity. Gender nonconformity, or the perception that an individual fails to conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 77 publications
2
46
0
Order By: Relevance
“…Findings from the U.S. suggest that transgender individuals experience higher rates of stigma and discrimination than cisgender individuals and provides support for the gender minority stress framework (Martin-Storey & August, 2015; Shipherd, Maguen, Skidmore, & Abramovitz, 2011). One study using data collected in the U.S. estimated that 98% of transgender individuals reported one or more traumatic events in their lifetime, relative to 56% of cisgender women and men from the general population (Shipherd, Maguen, Skidmore, & Abramovitz, 2011).…”
mentioning
confidence: 69%
“…Findings from the U.S. suggest that transgender individuals experience higher rates of stigma and discrimination than cisgender individuals and provides support for the gender minority stress framework (Martin-Storey & August, 2015; Shipherd, Maguen, Skidmore, & Abramovitz, 2011). One study using data collected in the U.S. estimated that 98% of transgender individuals reported one or more traumatic events in their lifetime, relative to 56% of cisgender women and men from the general population (Shipherd, Maguen, Skidmore, & Abramovitz, 2011).…”
mentioning
confidence: 69%
“…Focusing on the top-ranked peer-reviewed articles in a specific research field can bring with it both an understanding of the knowledge produced in the field, but also give an interesting picture of normative understandings of the research subject per se. Therefore, in order to contextualize and guide a discussion about challenges and limitations recurrent in the research field as a whole, this section summarizes main findings from topranked peer-reviewed articles in the research field on sexual harassment in higher education (Adams, Kottke, and Padgitt 1983;Benson and Thomson 1982;Bruce et al 2015;Cantalupo 2014;Clancy et al 2014;Coker et al 2015Coker et al , 2016Cortina et al 1998;D'augelli 1992;Finn 2004;Fnais et al 2014;Gelfand, Fitzgerald, and Drasgow 1995;Gersen and Suk 2016;Herek 1993;Kenig and Ryan 1986;Komaromy et al 1993;Magnavita and Heponiemi 2011;Martin-Storey and August 2016;Nora et al 2002;Ong 2005;Padgitt and Padgitt 1986;Reilly, Lott, and Gallogly 1986;Robnett 2016;Schneider 1987;Schneider, Swan, and Fitzgerald 1997;Selkie et al 2015;Settles et al 2006;Somers 1982;Wolf et al 1991).…”
Section: Top-ranked Peer-reviewed Articlesmentioning
confidence: 99%
“…Li, Kung, and Hines (2017), for example, found that caregiver-rated gender nonconforming behavior as early as age 4 was positively associated with youth having a gay/lesbian identity at age 15 (see also Steensma, van der Ende, Verhulst, & Cohen-Kettenis, 2013). Early gender nonconformity may, therefore, be uniquely important in explaining variation in victimization within sexual minorities (Toomey et al, 2010), and between sexual minorities and heterosexual individuals (Martin-Storey & August, 2016;Rieger & Savin-Williams, 2012). These findings suggest that the vulnerability to negative social outcomes among sexual minority youth may emerge prior to adolescence, and that more information is needed on this topic to inform intervention and prevention programming.…”
Section: Prior Longitudinal Researchmentioning
confidence: 99%